Mekanisme Penentuan Harga Jual Dan Profit Margin Pembiayaan Murabahah Di PT. Bank Sumut Syariah KCP Stabat - Sarmila Sarmila; Diyan Yusri; Anjur Perkasa Alam (Yayasan Rahmat Islamiyah, 2023)
This study focuses on the discussion of the mechanism for determining the selling price and profit margin of murabahah financing at PT. Bank SUMUT Syariah KCP Stabat and the factors that influence it. The research method used in this study is a descriptive qualitative research method with an empirical approach. Informants in this study were employees of PT. Bank SUMUT Syariah KCP Stabat. The results of the study explain that the mechanism for determining the selling price and profit margin of murabahah financing is carried out by PT. Bank SUMUT Syariah KCP Stabat uses the flat profit method where the calculation of profit margins on the value of the cost of financing is fixed from one period to another.